Developing creativity in higher education for 21st century learners: A protocol for a scoping review. (2017) - Egan, Arlene; Maguire, Rebecca; Christophers, Lauren; Rooney, Brendan
Highlights: Creativity has been widely acknowledged as a key skill for 21st century learning, yet it is unclear how best to develop it in higher education. This protocol suggests a scoping study be conducted to identify the frameworks being used to explicitly develop student's levels of creativity. The protocol also suggests the identification of the characteristics of creativity that educators associate with their creativity frameworks. By using the ideas developed originally by Arksey and O'Malley (2005) a 6 stage framework has been proposed to support a scoping study. The findings will serve to enhance our understanding of the value that higher level educators are placing on creativity in educational contexts. Abstract: There is an abundance of literature highlighting the need to focus on enhancing students' creativity in higher education. However, currently there is a gap in awareness of evidence-based initiatives being employed in institutions to address this need. The debate on how to best characterise creativity has not yet reach consensus therefore, we present a protocol for a new review that will identify the characteristics of the frameworks as well as the tools being used by educators to formally develop students' creativity in higher education. It will also provide insight into how these educators are defining creativity. This knowledge will enhance understanding of how creativity, a necessary skill for 21st century learners is being harvested, valued, and described in higher education.